Presence of sulfonamide and carbapenem resistance genes in a sewage treatment plant in southeast Louisiana, USA. (October 2017) - Naquin, Tad; Robichaux, Katie; Belding, Cameron; Bergeron, Scott; Boopathy, Raj
Abstract: To date only sporadic studies have reported the occurrence of carbapenem and sulfonamide resistance genes in rural sewage treatment plants of USA. Most of the reports on this subject are from hospitals and urban aquatic habitats. Therefore, this study was conducted to find the presence of these genes in a rural sewage treatment plant in southeast Louisiana, USA. Raw and treated sewage samples were analyzed for five months in 2016 for the presence of antibiotic resistance genes. The results showed the presence of carbapenem and sulfonamide resistance genes in both raw and treated sewage. Many sulfonamide and piperacillin resistant bacteria were consistently present in raw and treated samples. This is the first report on the presence of carbapenem resistance genes in a small town sewage treatment plant in USA. Carbapenem possesses potent antibiotic capabilities coupled with inhibition of bacterial enzymes and it has been the last resort of physician's medication to treat infection from many multidrug resistant bacteria. The presence of carbapenem resistance genes in treated sewage sample is a cause for concern and further research should be done to see how prevalent these genes are in many aquatic habitats including rural sewage treatment plants, which in many cases discharge the treated sewage into nearby streams and rivers and may act as a reservoir for these genes in the environment. Highlights: Antibiotic resistant bacteria were found in the raw and treated sewage. Many antibiotic resistance genes were found in the treated sewage. Specific carbapenem resistance genes such as KPC and OXA-48 were found in the treated sewage. Sewage treatment plant may play a role in spreading of many antibiotic resistance genes in the aquatic habitat.